2020
DOI: 10.1038/s41416-020-0764-3
|View full text |Cite
|
Sign up to set email alerts
|

A common polymorphism in the retinoic acid pathway modifies adrenocortical carcinoma age-dependent incidence

Abstract: BACKGROUND: Genome-wide association studies (GWASs) have enriched the fields of genomics and drug development. Adrenocortical carcinoma (ACC) is a rare cancer with a bimodal age distribution and inadequate treatment options. Paediatric ACC is frequently associated with TP53 mutations, with particularly high incidence in Southern Brazil due to the TP53 p.R337H (R337H) germline mutation. The heterogeneous risk among carriers suggests other genetic modifiers could exist. METHODS: We analysed clinical, genotype an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Then two datasets including GSE75415 ( West et al, 2007 ) and GSE12368 ( Soon et al, 2009 ) were included. Then four datasets including GSE76021 ( Pinto et al, 2016 ), GSE19750 ( Demeure et al, 2013 ), GSE10927 ( Giordano et al, 2009 ), and GSE76019 ( Surakhy et al, 2020 ) from this database were collected and used in the present study, because of the complete clinical and survival information they contained. Moreover, we retrieved microarray data of ACC (TCGA-ACC data) and the related clinical information via The Cancer Genome Atlas (TCGA) database ( https://genome-cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Then two datasets including GSE75415 ( West et al, 2007 ) and GSE12368 ( Soon et al, 2009 ) were included. Then four datasets including GSE76021 ( Pinto et al, 2016 ), GSE19750 ( Demeure et al, 2013 ), GSE10927 ( Giordano et al, 2009 ), and GSE76019 ( Surakhy et al, 2020 ) from this database were collected and used in the present study, because of the complete clinical and survival information they contained. Moreover, we retrieved microarray data of ACC (TCGA-ACC data) and the related clinical information via The Cancer Genome Atlas (TCGA) database ( https://genome-cancer.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the association of 11p15 or TP53 genes with abnormal activity of phosphodiesterases has been reported (45). Genome-wide association studies (GWAS) based on single nucleotide polymorphism (SNP) assays identified retinoic acid pathway anomalies in adrenocortical carcinoma (46). MEN type 1 syndrome caused by MEN1 gene mutation, which is associated with pituitary tumors or gastrointestinal and pancreatic neuroendocrine neoplasia has been reported to be present in adrenal tumors (47)(48)(49).…”
Section: Associated Genetic Backgroundmentioning
confidence: 99%
“…In one study variants of Epidermal Growth Factor Receptor (EGFR) were identified at higher incidence in children and young adults ACC [ 32 ]. Polymorphisms of selected genes could have influence on ACC incidence (retinoic acid pathway genes) [ 33 ], ACC tumorigenesis (phosphodiesterases genes) [ 34 ] or response to mitotane treatment (P450 cytochrome genes) [ 35 ]. Twelve single case reports expanded the catalog of single or multiple variants described in ACC.…”
Section: Systematic Analysis Of Literature 2019–2021 Of Molecular Gen...mentioning
confidence: 99%